The Relationship Between Physical Activity and Nutritional Status with Early Menarche in School Age Children in Bekasi City - Qothrunada Salsabila; Arindah Nur Sartika; Afrinia Ekasari; Guntari Prasetya (Journal of Global Nutrition, 2025)
Early menarche is the first menstruation in girls that occurs at the age of under 12 years. Early menarche is an important phenomenon that can affect the health and development of girls. Early menarche can cause several other health problems such as breast cancer in girls due to longer exposure to estrogen and progesterone. This study aims to analyze the relationship between nutritional status and physical activity with early menarche in school-age children in Bekasi City. This study was conducted in East Bekasi District, which is one of the districts in Bekasi City with a fairly heterogeneous female population with a sample of 122 female students taken using the consecutive sampling method. This study uses a quantitative approach with a cross-sectional design, which allows researchers to collect data simultaneously on independent variables (nutritional status and physical activity) and dependent variables (early menarche). Data were collected through questionnaires, and will be analyzed using appropriate statistical methods to determine the relationship between the variables studied.